Le révélateur - Shafto, Sally; Lastens, Emeric de (Re:Voir, 2006)
"The Zanzibar Group (also known as Zanzibar Films) was a radical French collective of filmmakers active from 1968 to 1970. The group included filmmakers Philippe Garrel and Jackie Raynal. Sally Shafto has referred to them as "the Dandies of May 1968", in reference to the civil unrest in France at the time. [...] The group's work was financed by Sylvina Boissonnas. Productions were sparse: directors shot without scripts and actors were typically not paid for their work. The group shot on expensive 35 mm film. In 1969, several members of the group embarked on a trip to Africa to shoot Serge Bard's film Au-delà. However, Bard abandoned the project before reaching their namesake destination. The Zanzibar group dissolved when Boissonnas stopped financing their films and instead became more active in the French feminist movement. Boissonnas was unable to sell the rights to the group's films to distributors, and so the group's work remained relatively unknown until a 2000 screening at the Cinémathèque Française" [https://en.wikipedia.org/wiki/Zanzibar_Group]
Orig.: Frankreich, Ende Mai 1968
Enthält ein 32seitiges Booklet mit Texten zum Film und zur Gruppe Zanzibar von Sally Shafto und Emeric de Lastens
Experimenteller Stummfilm in Schwarz-Weiß, gedreht in München anlässlich der politischen Ereignisse Ende Mai 1968
Keywords: Film; DVD-Video